(untitled) (Proceedings International Conference on Fisheries and Aquaculture, 2024)
The escalation of marine litter, particularly microplastics originating from fishing and aquaculture activities, poses a significant threat to global ocean health and aquatic ecosystems. Despite growing awareness, the implementation of effective regulations and strategies to address this issue remains fragmented on a global scale. This article critically evaluates existing policies and proposes comprehensive strategies aimed at mitigating microplastic pollution in the fishing and aquaculture sectors. Drawing upon legislative databases, relevant literature, and expert recommendations, the article highlights the strengths and limitations of current approaches while advocating for a unified global effort towards sustainable marine resource management.